High-temperature electrothermal remediation of multi-pollutants in soil - Bing Deng; Robert A. Carter; Yi Cheng; Yuan Liu; Lucas Eddy; Kevin M. Wyss; Mine G. Ucak-Astarlioglu; Duy Xuan Luong; Xiaodong Gao; Khalil JeBailey; Carter Kittrell; Shichen Xu; et al. (Nature Communications, 2023)
Abstract Soil contamination is an environmental issue due to increasing anthropogenic activities. Existing processes for soil remediation suffer from long treatment time and lack generality because of different sources, occurrences, and properties of pollutants. Here, we report a high-temperature electrothermal process for rapid, water-free remediation of multiple pollutants in soil. The temperature of contaminated soil with carbon additives ramps up to 1000 to 3000 °C as needed within seconds via pulsed direct current input, enabling the vaporization of heavy metals like Cd, Hg, Pb, Co, Ni, and Cu, and graphitization of persistent organic pollutants like polycyclic aromatic hydrocarbons. The rapid treatment retains soil mineral constituents while increases infiltration rate and exchangeable nutrient supply, leading to soil fertilization and improved germination rates. We propose strategies for upscaling and field applications. Techno-economic analysis indicates the process holds the potential for being more energy-efficient and cost-effective compared to soil washing or thermal desorption.